181k views
5 votes
3(-2 - n) = -9 -4n answer

1 Answer

1 vote

Answer:

n = -3

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define equation

3(-2 - n) = -9 - 4n

Step 2: Solve for n

  1. Distribute 3: -6 - 3n = -9 - 4n
  2. Add 4n to both sides: -6 + n = -9
  3. Add 6 to both sides: n = -3

Step 3: Check

Plug in n to verify it's a solution.

  1. Substitute: 3(-2 - -3) = -9 - 4(-3)
  2. Simplify: 3(-2 + 3) = -9 - 4(-3)
  3. Add: 3(1) = -9 - 4(-3)
  4. Multiply: 3 = -9 + 12
  5. Add: 3 = 3
User Smartie
by
5.9k points